2018
DOI: 10.17546/msd.399388
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of dyspeptic symptoms and endoscopic findings in diabetic patient

Abstract: Objective:We aimed to demonstrate the relationship between the endoscopically increased mucosal damage and the frequency of dyspeptic symptoms in patients with diabetes. Material and Methods:The 42 diabetic patients with dyspeptic complain and 40 healthy dyspeptic people were involved in this study and evaluated with video endoscopes.Results: Diabetic patients when compared with the control group according to the endoscopic evaluation and Glasgow Dyspepsia Symptom Scoring System no significant difference had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Similar studies have demonstrated a relationship between dyspeptic complaints and diabetic regulation, with dyspeptic complaints being higher in DM patients with poor glycemic control [19,20]. In the study conducted by Oner et al, who investigated frequency of dyspeptic complaints among diabetic and non-diabetic patients, it was reported that dyspeptic complaints were significantly higher in DM patients [19]. Although dyspeptic complaints are frequent in DM patients, it is not clear whether there is any difference between non-diabetic patients in terms of endoscopic findings, with conflicting results reported [19][20][21][22].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Similar studies have demonstrated a relationship between dyspeptic complaints and diabetic regulation, with dyspeptic complaints being higher in DM patients with poor glycemic control [19,20]. In the study conducted by Oner et al, who investigated frequency of dyspeptic complaints among diabetic and non-diabetic patients, it was reported that dyspeptic complaints were significantly higher in DM patients [19]. Although dyspeptic complaints are frequent in DM patients, it is not clear whether there is any difference between non-diabetic patients in terms of endoscopic findings, with conflicting results reported [19][20][21][22].…”
Section: Discussionsupporting
confidence: 61%
“…Although dyspeptic complaints are frequent in DM patients, it is not clear whether there is any difference between non-diabetic patients in terms of endoscopic findings, with conflicting results reported [19][20][21][22]. In a comparison of endoscopic findings between two groups of patients, Oner et al showed that the frequency of gastric ulcers was higher in DM patients, but there was no significant difference in terms of other endoscopic findings [19]. Koch et al found no correlation between glycemic control and dyspeptic complaints and endoscopic findings [9].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Sedangkan untuk frekuensi kejadian ulkus pada komorbid hipertensi, diabetes dan CVD berhubungan dengan terapi pengobatan dari komorbid dimana penggunaan antiplatelet atau anti koagulan seperti, aspirin, cropidogel pada ke 3 komorbid tersebut dapat memicu kerusakan pada mukosa lambung (22), (23).…”
Section: Profil Pasien Berdasarkan Komorbidunclassified